2008
DOI: 10.1159/000114094
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Effects of Food Intake during Haemodialysis

Abstract: Background: There is some doubt whether food intake during haemodialysis (HD) is detrimental to haemodynamic stability. Methods: We studied 20 stable non-diabetic HD patients during a single session. A standard meal was given 45 min into dialysis. Relative blood volume (RBV), cardiac output (CO), systemic vascular resistance (SVR) and extracellular fluid (ECF) resistance were monitored continuously. Total protein and albumin were measured. Results: There was a significant reduction in RBV after food ingestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…In this regard, Kistler et al, 16 have found that people who consumed food during hemodialysis suffered from hypotension. However, the results of Sivalingam et al, 27 study, showed a significant decrease in blood pressure 30 minutes after food intake which was consistent with the present study. Also Kara & Acikel 1 investigated the effect of standard meal in 25 hemodialysis patients and found that hypotension created no problem.‏ Muller‏ et al, 28 study can be noted as another conflicting study.…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, Kistler et al, 16 have found that people who consumed food during hemodialysis suffered from hypotension. However, the results of Sivalingam et al, 27 study, showed a significant decrease in blood pressure 30 minutes after food intake which was consistent with the present study. Also Kara & Acikel 1 investigated the effect of standard meal in 25 hemodialysis patients and found that hypotension created no problem.‏ Muller‏ et al, 28 study can be noted as another conflicting study.…”
Section: Discussionsupporting
confidence: 93%
“…Intradialytic food ingestion therefore causes hypotensive attacks by decreasing the cardiac output (12,13,32). A recent study involving 20 stable nondiabetic patients found that food intake during HD caused significant reductions in relative blood volume ( 17). Intradialytic food consumption and intradialytic hypotension also influence the adequacy of the treatment (18>33).…”
Section: Discussionmentioning
confidence: 99%
“…It is important for healthcare staff to be aware of the problems tbat can be caused by intradialytic food intake and to develop feeding protocols in line witb the clinical evidence (13). Several studies bave been conducted to assess tbe bemodynamic effects of intradialytic food ingestion (14)(15)(16)(17). However, little is known about the relationship between intradialytic food intake and urea kinetic parameters (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…In healthy subjects eating increases both splanchnic and hepatic blood flow [58]. There is a drop in systemic vascular resistance, accompanied by an increase in both heart rate and cardiac output to maintain blood pressure [59–61]. However, postprandial hypotension is seen particularly in patients with autonomic dysfunction, patients with hypertension, elderly patients, patients with cardiovascular disease, and patients with renal failure on HD [62].…”
Section: Central Venous Oxygenation During Hdmentioning
confidence: 99%